Identifying the Combinations of Perceived Value and User Features for Enhancing Continuance of Theme Park Apps: A fsQCA Approach - Long, Ting; Suomi, Reima (United States, 2025)
Drawing on perceived value theory, this study applies a fuzzy-set qualitative comparative analysis (fsQCA) to examine how different combinations of sub-dimensions of perceived value (including functional, convenience, hedonic, and social value), together with user features (smartphone use habit and travel frequency to theme parks) motivate users to continue using a theme park app from a configurational approach. Further, the functional value was proposed to include five components: real-time information, map navigation, online order, virtual queue, and recommended routes. By analyzing empirical data collected via an online survey in China (N = 347), this study found six different configurations of causal conditions for inducing continuance usage. Particularly, online order and perceived convenience value are found to be core conditions reinforcing continuance usage in combination with different peripheral conditions. This study contributes to the literature by offering new insights into IS continuance from a configuration perspective in a theme park app context.
PACIS 2023 Proceedings